Forecasting Teaching and Learning Outcomes Effects of Mathematics Courses in the Mechatronics Engineering Degree at UTB - Noaman, Noaman M.; Calucag, Lina S.; Aleta, Beda T.; Ahmed, Husham M. (IEEE International Conference on Engineering Technologies and Applied Sciences (Online), 2023)
The impact of mathematics courses within specialization tracks on student performance in engineering programs holds substantial importance, underscoring the necessity for faculty to consistently assess and enhance the curriculum to adequately equip students for the demands of the engineering domain. A descriptive research design was employed to assess the influence of mathematics courses on the attainment of mechatronics engineering competencies at the University of Technology Bahrain. We analyzed all assessments of 10 mathematics and 18 professional courses during the academic year 2021-2022. Our aim was to assess the effectiveness of integrating mathematics courses into the teaching of specialization courses and its impact on student outcomes (SO1-SO7). The results indicate that several mathematics courses had a significant influence on the achievement of these outcomes, except for SO4. Notably, Probability and Statistics (57.14%), Calculus II (60.11%), Numerical Methods (64.32%), Advanced Math (67.19%), and Linear Algebra (71.42%) demonstrated substantial effects on student outcomes. In contrast, Discrete Mathematics showed the most pronounced impact with an 85.71% effect on all SOs through the specialization courses. Conversely, College Algebra and trigonometry and Partial Differential Equations (14.28%), Multivariate Calculus (19.25%), and Optimization (28.57%) had a relatively lower impact on enhancing SOs in mechatronics engineering. To further improve student outcomes, we recommend revising the mathematics syllabus to incorporate topics such as laws of logic, rules of inferences, quantifiers, proofs of theorems, set theory, trees and sorting, shortest path and minimal spanning trees algorithms, Monoids and Groups, Laplace and inverse Laplace transform, and applications of differentiation and integrations. Integrating these topics will enhance the teaching and learning of specialization courses, ultimately leading to improved attainment of mechatronics engineering attributes.